Exploring Students’ Motivational Regulation Strategies in Writing Argumentative Essays - Anggi Ratri Anggoro Kasih; Ahmad Munir (Universitas Muhammadiyah Barru, 2023)
This research aimed to find out the motivational regulation strategies employed by English education students when writing argumentative essays and to describe how English education students employ motivational regulation strategies when writing argumentative essays. This mixed-methods research used a sequential explanatory strategy. The research subjects were 95 English education students of a state university in Surabaya. They were asked to complete a self-report questionnaire. Nine of them were interviewed using a stimulated recall protocol. Questionnaire data were analyzed using descriptive statistics while the interview data were analyzed using spiral analysis. It was found that environmental structuring and emotional control are the most commonly used motivational regulation strategies when writing argumentative essays. They usually connect their essays to their interests in education and social issues even though most lecturers did not allow students to choose their topics. Performance self-talk is the rarest motivational regulation strategy used the participants as they do their essay only to meet the requirements of the course. It is suggested that students realize the benefit of argumentative writing skills for them and the lecturers give their students the independence to choose their topic, as it can motivate them to write.